PENGEMBANGAN MODEL PEMBELAJARAN ADEL (ACTIVE AND DELIGHTFUL LEARNING) PADA MATERI ORGANEL SEL KELAS VII SMP - Adella Putri Kasih; Heru Nurcahyo (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2020)
DEVELOPMENT OF THE ADEL LEARNING MODEL ON CELL ORGANELLE TOPIC FOR GRADE 7 JUNIOR HIGH SCHOOL AbstractThis study aims to create the ADEL learning model on the subject of cell organelles for grade 7 students of junior high school. This ADEL learning model is a combination of two learning approaches, the SAVI approach and accelerated learning. This research was conducted in four stages: define, design, develop, disseminate. Data collected were using instruments, including product assessment sheets in the form (aspects of content validity, construction, and practicality) and student questionnaire responses. Product trials are conducted with limited trials and large group trials. The test subjects were 35 students of grade 7 SMPN 15 Yogyakarta. The results of the analysis of the aspects of the validity of the ADEL learning model reach valid criteria, the practical aspects of the ADEL learning model have very good criteria and show that the ADEL learning model is quite practical. Moreover, students' responses to the ADEL learning model received good responses. The ADEL learning model on cell organelle material for 7th-grade junior high school students has valid and practical criteria so that it can be implemented in the learning process. AbstrakPenelitian ini bertujuan untuk menghasilkan model pembelajaran ADEL pada materi organel sel kelas VII SMP. Model pembelajaran ADEL ini merupakan kombinasi dari 2 pendekatan pembelajaran yaitu pendekatan SAVI dan Accelerated Learning. Penelitian ini merupakan penelitian pengembangan (R&D) dengan model 4-D yang terdiri atas Tahap define, design, develop, disseminate. Pengambilan data menggunakan lembar angket penilaian produk yang berupa (aspek validitas isi & konstruk serta kepraktisan) dan angket respon peserta didik. Uji coba produk dilakukan dengan uji coba terbatas dan uji coba kelompok besar. Subjek uji coba yaitu 34 peserta didik kelas VII SMP N 15 Yogyakarta. Hasil penelitian menunjukkan bahwa: model pembelajaran ADEL pada materi organel sel kelas VII SMP layak digunakan dalam proses pembelajaran. Hasil analisis aspek validitas model pembelajaran ADEL mencapai kriteria valid, aspek praktis model pembelajaran ADEL memiliki kriteria sangat baik dan menunjukkan bahwa model pembelajaran ADEL cukup praktis. dan tanggapan peserta didik terhadap model pembelajaran ADEL mendapatkan tanggapan yang baik. Model pembelajaran ADEL pada materi organel sel untuk peserta didik kelas 7 SMP memiliki kriteria yang valid dan praktis. sehingga dapat diimplementasikan dalam proses pembelajaran.